Pelatihan dan Pendampingan Penyusunan Penilaian HOTS bagi Guru SD - Manar Imam Muhammadi; Dwi Priyo Utomo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aimed to improve elementary school teachers’ competence in developing Higher Order Thinking Skills (HOTS)-based assessment instruments through training and mentoring. The activity involved 20 elementary school teachers and was conducted through several stages, including needs analysis, HOTS assessment training, hands-on practice with intensive mentoring, and evaluation using pre-tests, post-tests, assessment quality analysis, and questionnaires. The results showed an improvement in teachers’ understanding, indicated by an increase in the average score from 45 in the pre-test to 78 in the post-test. In addition, the proportion of HOTS items developed by teachers increased from 20% to 75% after the training and mentoring activities. Teachers reported that the program was practical and helped them design assessment instruments that require higher-order thinking skills. Overall, this activity demonstrates that training combined with mentoring is effective in enhancing teachers’ competence in HOTS-based assessment.